A Clinico-Biochemical Correlation among Body Mass Index and Oral Health Status Regarding Decayed, Missing, and Filled Permanent Teeth Index in Children - Muhammad Asim, Maria Ilyas, Nauman Bari Khan, Misbah Ali, Ayesha Yasir, Mamoona Shuja, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Overweight and obesity caused dental caries in young children, the Decayed, Missing, and Filled Teeth (DMFT) index is primary population-based indicator. Objectives: This study aimed to assess the impact of obesity and overweight on children's blood biochemistry parameters and oral/dental health. Methods: The study included ninety-two children (40 boys and 52 girls), who presented to our pediatric clinic with age of 10 to 18 years. The parameters such as age, gender, BMI, Decayed, Missing, and Filled Teeth Index (DMFT), salivary pH, Salivary Flow Rate, Calcium and Phosphorus Levels in saliva were measured. The mean standard deviation was used to find out the normal levels of continuous variables distribution. The data within the subgroups were analyzed by two-way ANOVA and criteria of significant p-value was recommended low than (P<0.05). Results: Obese children (Group B) showed significantly higher DMFT scores and lower salivary pH, flow rate, calcium, and phosphorus levels compared to normal-weight children (Group A) (p < 0.05). Specifically, the mean DMFT index was 6 for obese males and 5 for obese females, compared to 2 for normal-weight males and 3 for normal-weight females. Salivary calcium and phosphorus levels were significantly lower in obese children, with p-values less than 0.001. Conclusion: The study concludes that there is a significant association between higher BMI and poorer oral health outcomes in children, as evidenced by increased DMFT scores and altered salivary biochemistry. These findings emphasize the need for targeted oral health interventions in overweight and obese children. Keywords: Decayed, Missing, and Filled Teeth (DMFT) index, body mass index, Salivary Flow Rate, Oral Health, Salivary Calcium.